EMPOWERING ABU CANGKANG KELAPA SAWIT TERHADAP KUALITAS BATA BETON RINGAN (LIGHT-WEIGHT CONCRETE) - Istianto Budhi Rahardja; Vianda Nia C. Surbakti; Ahdiat L Siregar (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
This research aims to determine the effect of adding oil palm shell ash on the quality of the resulting lightweight concrete bricks. Based on SNI 03-2847-2002, lightweight concrete is concrete containing light aggregate and unit weight between 800-1900 kg / m³. Making lightweight concrete bricks requires other materials in the mixing process, including silica sand. Silica sand is a major structural component in building and construction products, has the chemical formula SiO2 (silicon dioxides) which can be obtained from mineral, vegetable, and synthetic silica. Palm ash has pozzolanic properties and contains silica elements ranging from 31.45%, so that this element can be mixed with cement and produce higher mortar strength. In this research, the composition of the shell ash used was 15%, 30% and 45%, with variations in the composition of other ingredients. The results of calculations and testing, the addition of palm shell ash gave the quality of lightweight concrete bricks at 30% composition, with compressive strength: 13.43 MPa, density: 1.112.3 kg / m³ and water absorption capacity: 28.7%.